2018
DOI: 10.1111/cpr.12437
|View full text |Cite
|
Sign up to set email alerts
|

PLCγ2 promotes apoptosis while inhibits proliferation in rat hepatocytes through PKCD/JNK MAPK and PKCD/p38 MAPK signalling

Abstract: This study showed that PLCγ2 regulates hepatocyte growth through PKCD-dependently activating p38 MAPK and JNK MAPK pathways; this result was experimentally based on the further exploration of the effect of PLCγ2 on hepatocyte growth in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…The JNK signalling pathway is tightly regulated and is implicated in a plethora of cellular function . However, the molecular mechanism that modulates the JNK signalling pathway remains elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The JNK signalling pathway is tightly regulated and is implicated in a plethora of cellular function . However, the molecular mechanism that modulates the JNK signalling pathway remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…The JNK signalling pathway is tightly regulated and is implicated in a plethora of cellular function. 45,46 However, the molecular mechanism that modulates the JNK signalling pathway remains elusive. Here, we reported that FER was able to positively regulate JNK signalling, which was supported by several lines of evidence.…”
Section: Discussionmentioning
confidence: 99%
“…In combination with various databases and preliminary screening results, we selected three typical mRNAs for further verification. For example, PLCG2 could promote proliferation through inactivating ERK and NF-κB pathway ( Ma et al, 2019 ), p38 MAPK and JNK MAPK pathways ( Chen et al, 2018a ), PKCδ-mediated JNK1/2 signaling pathway ( Chen et al, 2018b ). The TPR contributes to the organization of the nuclear lamina and in cooperation with lamins guards the interphase assembly of nuclear pore complexes ( Fišerová et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…MAPK is a class of serine/threonine-protein kinases, including three main types of subfamily members: the extracellular-signal-regulated kinases (ERKs), the c-jun N-terminal kinase (JNKs), and the p38 kinases ( Lee et al, 2020 ; Sinkala et al, 2021 ). They can transfer the extracellular signals into the nucleus via the MAP3K–MAP2K–MAPK cascade to participate in cellular activities like proliferation, differentiation, and apoptosis ( Chen et al, 2018 ; Ostojic et al, 2021 ). It was reported that bone marrow stem cell-derived extracellular vesicles (BMSC-EVs) could alleviate the IL-1β-induced chondrocyte inflammatory phenotype ( Zhang B et al, 2022 ), and such effect was further improved with the treatment of BMSC-EV generated in a hypoxic environment.…”
Section: Mir-17-92 In Cartilage Degradationmentioning
confidence: 99%